Kahn and the XX Century: A. Rappaport’s Review of P. Kapustin’s Essay Accompanied by the Author’s Comments - Kapustin, Petr; Rappaport, Alexander (project baikal, 2019)
The authors discuss the significance of L. Kahn for culture of the XX century. In the period of transition from modernism to postmodernism, Kahn remained a unique figure: he took upon himself all the problems of the destroyed and unfinished architecture. They point out his distinctiveness and relation to the transition from avant-garde to modernism. They discuss the phenomenon of subjectiveness of architectural criticism.
Keywords: Louis Kahn; architectural style; individuation; avant-garde; architectural criticism; modernity